Creating Value in a Retail Business. Evidence From the Russian Food Retail Market - Vashakmadze, Teimuraz; Martirosyan, Emil; Sergeeva, Anastasia (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2015)
Teimuraz Teimurazovich Vashakmadze - Director of the Master’s program, assistant professor of business and management strategy, IBDA RASHiGS under the President of the Russian Federation. Emil G. Martirosyan Anastasia Alexandrovna Sergeeva In the post crisis years, the Russian food retail market has skyrocketed and run ahead of the market in general. Our research reveals major value drivers and explores the value creation of companies by comparison based on a P/B ratio. The analysis of performance indicators of the three biggest Russian food retailers provides evidence suggests that ROE can explain the difference and positive relationship of a P/B ratio. Our findings suggest that retail companies are increasing ROE through net profit margin improvement. In addition, we found out that a higher Store/DC ratio has a strong correlation to the ROE of a company. The key question of the paper is identifying a combination of factors that drive performance and value creation in post-crisis period in non-consolidated Russian food retail market. Thus, our research is aimed at providing a broader picture of factors that influence value creation in a retail market, such as cross-docking, franchising, recognition of product matrix, management decision decentralization, focusing on core activity and commercial conditions with suppliers. In this article we have explained the business factors that mostly influenced the corporate ROE and the price-per-book value of the company of the Russian food retail industry. After the analysis of three Russian retail chains we have come to the conclusion that the retail business development in Russia (apart from the consumer market factors) mostly depends on efficient management in operations and on having good commercial conditions with suppliers. At the same time there is a direct impact on the retailers’ gross margins from the specific operational solutions like crossdocking implementations.